Cover Picture: Plasma Process. Polym. 9/2019. Issue 9 (5th September 2019) - Marchack, Nathan; Hernandez, Keith; Walusiak, Benjamin; Innocent‐Dolor, Jon‐l; Engelmann, Sebastian
Abstract : Front Cover : The ability to control individual step parameters in cyclic plasma etch processes provides novel capabilities for nanofabrication. In this example, the pitch of a line/space array is halved as the pattern is transferred into a tantalum nitride (TaN) film. The redeposition of a partially oxidized surface layer creates a self‐aligned mask, and line edge roughness (LER) is maintained by the highly selective nature of the etch. Further details can be found in the article by Nathan Marchack, Keith Hernandez, Benjamin Walusiak, Jon‐l Innocent‐Dolor, Sebastian Engelmann (1900008 ).